Polymerizable monomer composition for dental restorations and its method of manufacture and use
By adding crosslinking agents to dental restoration materials, the mechanical properties and biocompatibility of resin ceramic restoration materials are improved, and the problems of insufficient mechanical properties and short service life of existing materials are solved, and high-strength and low-absorbent dental restoration materials are achieved.
Patent Information
- Application Number
- JP2022550800
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-07-21
- Filing Date
- 2022-07-08
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-07-08
AI Technical Summary
Existing dental restoration materials have problems such as poor mechanical properties, high water absorption value, poor thermal stability and short service life. In particular, resin ceramic restoration materials cannot meet the fully satisfactory mechanical performance requirements in practical applications.
By adding crosslinking agents to dental restoration materials, a polymerizable monomer composition with high conversion double bonds is formed, crosslinking density is improved, mechanical properties and biocompatibility of resin ceramic restoration materials are enhanced, and water absorption and dissolution value is reduced.
It improves the bending strength and hardness of resin ceramic restoration materials, reduces water absorption and dissolution value, ensures that the material is not prone to cracking or disintegrating during dental restoration, extends its service life, and is suitable for permanent restoration.
Smart Images

Figure 0007628130000001
Abstract
Description
[Technical field]
[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims priority to a Chinese patent application filed with the China Patent Office on July 21, 2021, with application number 202110826681.7, entitled "Polymerizable monomer composition for dental restoration and its manufacturing method and use," the entire contents of which are incorporated herein by reference.
[0002] The present invention is in the field of composite materials, and specifically relates to a polymerizable monomer composition for dental restorations, and its preparation and use. [Background technology]
[0003] At present, digital restoration based on CAD / CAM technology has become an important development direction in oral restorative science. A variety of oral restorations can already be processed and manufactured by digital means. Among the dental restorative materials cut by CAD / CAM, ceramic materials are the most widely used materials in CAD / CAM technology due to their excellent mechanical properties, optical properties, and biocompatibility. However, ceramic materials are very brittle and prone to porcelain crack phenomenon, which causes great wear on the cutting bit, and also causes serious wear on the jaw teeth due to their high hardness. Resin materials occupy a large proportion in CAD / CAM cutting due to their low price, good toughness, easy machining and cutting, short repair cycle, and no wear on the jaw teeth. However, resin materials cannot be used as permanent restorative materials due to their low strength, poor wear resistance, and short service life.
[0004] Resin ceramic restorative materials combine the high strength of ceramic materials with the good toughness of resin materials, but there are two problems: (1) Resin ceramic restorative materials inherit the biocompatibility of ceramic materials to a certain extent, avoid the disadvantages of ceramic materials such as high strength, easy wear of jaw teeth, and easy brittle fracture, and also have significantly improved mechanical properties compared with resin materials, but in actual dental restorations, the mechanical performance of resin ceramic composite materials cannot reach a completely satisfactory level; (2) The high water absorption value of resin ceramic restorative materials will reduce the mechanical properties of the materials, cause microleakage, reduce the thermal stability of the materials, cause the precipitation of unreacted monomers in the materials, and even cause hydrolysis of polymer segments, ultimately shortening the service life of the materials.
[0005] Patent Document 1 discloses a polymerizable monomer composition for dental materials having a cured product that simultaneously achieves high toughness and rigidity, a composition for dental materials containing the polymerizable monomer composition for dental materials, and a cured product thereof with high mechanical properties. In the present invention, the polymerizable monomer composition for dental materials contains a urethane acrylate compound and a polymerizable compound, and the urethane acrylate compound is obtained by reacting a specific hydroxyacrylate with a diisocyanate, and the diisocyanate is formed by a bond between a methylene group, in which a hydrogen atom can be replaced by a hydrocarbon group, and two isocyanate groups by a divalent aromatic hydrocarbon group having 6 to 9 carbon atoms or a divalent crosslinked cyclic hydrocarbon group having 6 to 9 carbon atoms. The polymerizable compound contains at least one polymerizable group selected from a methacryloyl group and an acryloyl group. Patent Document 2 discloses a dental hardenable composition, in which the resin monomer and the filler are contained in a weight ratio of 10:90 to 70:30, and 0.01 to 10 parts by weight of a polymerization initiator and 0.001 to 1 part by weight of a terpenoid compound are contained relative to 100 parts by weight of the resin monomer. By adding a terpenoid compound as a chain transfer agent, the thermal polymerization rate of the resin monomer, which has a high thermal conductivity among the components contained in the dental hardenable composition and begins to polymerize rapidly due to heat, is slowed down, and thus uniform thermal polymerization is performed, the occurrence of microscopic and macroscopic strains is suppressed, and the occurrence of cracks and chips can be suppressed. In addition, the addition of this chain transfer agent suppresses the foaming of the low-boiling resin monomer, so that the inclusion of air bubbles can also be suppressed. However, the addition of the chain transfer agent and the design of the polymerizable monomer cannot improve the mechanical properties such as bending strength and hardness of the final ceramic resin material, and therefore cannot effectively improve the service life of the material.
[0006] Patent Document 3 discloses a thermosetting composite resin block, which is composed of a polymerizable resin containing an ethylenically unsaturated group, an initiator that dissolves in the resin and is activated at a temperature of about 100°C to about 150°C, and an inorganic filler mixed with the resin, and the bending strength, wear resistance, and aesthetic properties of the resin block are greatly improved. In addition, due to the high decomposition temperature of the initiator, it will not decompose prematurely into monomers under normal processing conditions, and the blank will not be discolored by the decomposition process. However, the improved mechanical strength is only 200 MPa, which cannot fully meet the needs of patients.
[0007] Therefore, the development of a polymerizable monomer composition to improve the mechanical properties, biocompatibility, and life span of resin ceramic restorative materials is an urgent technical problem for those skilled in the art to solve. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] CN106132383A [Patent Document 2] CN105310889A [Patent Document 3] CN102665605A Summary of the Invention [Problem to be solved by the invention]
[0009] In view of the deficiencies of the prior art, the present invention aims to provide a polymerizable monomer composition for dental restoration and its preparation method and use, the polymerizable monomer composition comprises a combination of a certain weight part of a polymerizable monomer, an initiator and a crosslinking agent, by adding the crosslinking agent, the double bond conversion rate of the polymerizable monomer composition is improved, the residual rate of the polymerizable monomer is reduced, after polymerization, the crosslinking density of the system is increased, the bending strength and hardness of the polymer are improved, and the water absorption value and dissolution value are reduced, and when applied to resin ceramic restorative materials, the mechanical properties and biocompatibility of the resin ceramic restorative materials can be effectively improved. [Means for solving the problem]
[0010] To this end, the present invention adopts the following technical solutions:
[0011] In a first aspect, the present invention provides a polymerizable monomer composition for dental restorations, said polymerizable monomer composition comprising the following components, by parts by weight: 20-100 parts by weight of a polymerizable monomer, 0.01-10 parts by weight of an initiator, and 0.01-10 parts by weight of a crosslinker.
[0012] In the present invention, the polymerizable monomer is preferably 25 parts by weight, 30 parts by weight, 35 parts by weight, 40 parts by weight, 45 parts by weight, 50 parts by weight, 55 parts by weight, 60 parts by weight, 65 parts by weight, 70 parts by weight, 75 parts by weight, 80 parts by weight, 85 parts by weight, 90 parts by weight, or 95 parts by weight. In the present invention, the weight parts of the polymerizable monomer are preferably all other point values between the above point values. Due to space limitations and for the sake of brevity, the present invention does not exhaustively recite the specific point values included in the ranges.
[0013] In the present invention, the initiator is preferably 0.2 parts by weight, 0.5 parts by weight, 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight or 9 parts by weight. In the present invention, the weight parts of the polymerizable monomer are preferably all other point values between the above point values. Due to space limitations and for the sake of brevity, the present invention does not exhaustively recite the specific point values included in the ranges.
[0014] In the present invention, the crosslinker is preferably 0.2 parts by weight, 0.5 parts by weight, 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, or 9 parts by weight. In the present invention, the parts by weight of the polymerizable monomer are preferably all other points between the above points, and due to space limitations and for the sake of brevity, the present invention does not exhaustively recite the specific points included in the ranges.
[0015] The polymerizable monomer composition for dental restoration provided by the present invention improves the double bond conversion rate of the polymerizable monomer by adding a crosslinking agent, and reduces the residual polymerizable monomer in the dental restoration material, thereby increasing the crosslink density of the polymerization system, thereby improving the bending strength and hardness of the polymer, and reducing its water absorption value and solubility value.
[0016] Preferably, the crosslinking agent is ethylene glycol dimethacrylate, 1,6-hexanediol dimethacrylate, Trimethylolpropane Trimethacrylate , trimethylolpropane triacrylate, divinylbenzene, acrylic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, methacrylic acid, hydroxyethyl methacrylate, hydroxypropyl methacrylate, or N-methylol acrylamide, or a combination of at least two of these.
[0017] Preferably, the polymerizable monomer is methyl methacrylate, ethyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, Isoamyl methacrylate , benzyl methacrylate, glycidyl methacrylate, dodecyl methacrylate, Tetrahydrofurfuryl methacrylate , 2-(Dimethylamino)ethyl methacrylate , 2,3-Dibromopropyl 2-methylpropenoate , 2-Hydroxyethyl methacrylate , 2-Hydroxypropyl methacrylate , 6-Hydroxyhexyl methacrylate , 10-Hydroxydecyl Methacrylate , triethylene glycol monomethacrylate, triethyl glycol dimethacrylate, propylene glycol monomethacrylate, ethylene glycol methacrylate, diethylene glycol methacrylate, methoxydiethylene glycol methacrylate, polyethylene glycol methacrylate, N-methylol (meth)acrylamide, N-succinyl (meth)acrylamide, 10-(meth)acryloyloxydecyl dihydrogen phosphate, Ethylene glycol di(meth)acrylate , Propylene glycol di(meth)acrylate , neopentyl glycol di(meth)acrylate, Butanediol di(meth)acrylate , Hexanediol di(meth)acrylate, polyethylene glycol di(meth)acrylate, urethane dimethacrylate, bisphenol A ethyl methacrylate, bisphenol A glycidyl (meth)acrylate (2,2-bis[4-[3-(meth)acryloyloxy-2-hydroxypropoxy]phenyl]propane), 2,2-bis[4-(meth)acryloyloxyethoxyphenyl]propane, 2,2-bis(4-(meth)acryloyloxydiethoxyphenyl)propane, 2,2-bis[4-(meth)acryloyloxypolyethoxyphenyl]propane, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, Tetramethylolmethane tri(meth)acrylate , Pentaerythritol tetra(meth)acrylate , ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, or N,N'-(2,2,4-trimethylhexamethylene)bis[2-(aminocarboxy)propane-1,3-diol]tetramethacrylate.
[0018] Preferably, the refractive index of the polymerizable monomer after polymerization is 1.52 to 1.58, preferably 1.525, 1.53, 1.535, 1.54, 1.545, 1.55, 1.555, 1.56, 1.565, 1.57 or 1.575. In the present invention, the refractive index of the polymerizable monomer after polymerization is preferably all other specific point values between the above point values, and due to space limitations and for the sake of brevity, the present invention does not exhaustively list the specific point values included in the above ranges.
[0019] Preferably, the initiator is dicumyl peroxide, tert-Butyl peroxide , benzoyl peroxide, lauroyl peroxide, tert-Butyl peracetate , Butyl tert-peroxybenzoate , Pivaloyl tert-butyl peroxide , potassium persulfate, sodium persulfate, ammonium persulfate, azobisisobutyronitrile , 2,2'-azobis(2,4-dimethylvaleronitrile) or 2,2'-Azobis(2-methylpropionate)dimethylThe present invention includes any one or a combination of at least two of the above.
[0020] In a second aspect, the present invention provides a method for producing a polymerizable monomer composition according to the first aspect, said method comprising mixing a polymerizable monomer, an initiator and a crosslinker to obtain said polymerizable monomer composition.
[0021] Preferably, the mixing time is 1 hour or more, preferably 1.1 hours, 1.2 hours, 1.3 hours, 1.4 hours, 1.5 hours, 1.6 hours, 1.7 hours, 1.8 hours, 1.9 hours, or 2 hours. The mixing time is preferably any other specific point value between the above point values. Due to space limitations and for the sake of brevity, the present invention does not exhaustively recite the specific point values included in the ranges.
[0022] Preferably, said mixing is carried out under stirring conditions, more preferably with a rotation speed of 20 r / min or more, said rotation speed being preferably 30 r / min, 40 r / min, 50 r / min, 60 r / min, 70 r / min, 80 r / min, 90 r / min or 100 r / min.
[0023] Preferably, the mixing temperature is below 50° C., and the mixing temperature is preferably 45° C., 40° C., 35° C., 30° C., 25° C., 20° C., 15° C., 10° C. or 5° C. The mixing temperature is preferably any other specific point value between the above point values. Due to space limitations and for the sake of brevity, the present invention does not exhaustively recite the specific point values included in the ranges.
[0024] In a third aspect, the present invention provides a resin ceramic repair material comprising the polymerizable monomer composition according to the first aspect and an inorganic filler.
[0025] In the resin ceramic restorative material provided by the present invention, by adding a polymerizable monomer composition containing a crosslinking agent, the obtained resin ceramic restorative material not only maintains its aesthetic appearance, but also improves its properties such as bending strength, water absorption value, and dissolution value, and the obtained resin ceramic restorative material has high strength and toughness, so that when this material is applied to dental restoration, it can maintain a good shape without phenomena such as collapse and cracking, regardless of the processing process or the process of wearing and using by the patient. In addition, due to the reduced water absorption value and dissolution value and the improved mechanical strength, its service life is extended and it can be used for permanent restoration, so that this material can be more widely used in dental restoration and meet the needs of the market.
[0026] Preferably, the resin ceramic restorative material comprises the following components in parts by weight: 10-90 parts by weight of the polymerizable monomer composition according to the first embodiment and 10-90 parts by weight of an inorganic filler.
[0027] In the present invention, the mass fraction of the polymerizable monomer composition is preferably 20 parts by weight, 30 parts by weight, 40 parts by weight, 50 parts by weight, 60 parts by weight, 70 parts by weight or 80 parts by weight. The mass fraction of the polymerizable monomer composition is preferably all other specific point values between the above point values. Due to space limitations and for the sake of brevity, the present invention does not exhaustively recite the specific point values included in the ranges.
[0028] In the present invention, the mass fraction of the inorganic filler is preferably 20 parts by weight, 30 parts by weight, 40 parts by weight, 50 parts by weight, 60 parts by weight, 70 parts by weight or 80 parts by weight. The mass fraction of the inorganic filler is preferably all other specific point values between the above point values. Due to space limitations and for the sake of brevity, the present invention does not exhaustively list the specific point values included in the range.
[0029] Preferably, the inorganic filler comprises any one or a combination of at least two of silica, aluminum silicate, alumina, calcium fluoride, strontium fluoride, calcium carbonate, kaolin, clay, mica, aluminum sulfate, calcium sulfate, barium sulfate, titanium oxide, calcium phosphate, hydroxyapatite, calcium hydroxide, strontium hydroxide, zeolite, titanium dioxide, or zirconia.
[0030] Preferably, the inorganic filler also includes a glass inorganic filler.
[0031] Preferably, the glass inorganic filler includes any one or a combination of at least two of fluorine glass, borosilicate glass, soda glass, barium glass, barium aluminosilicate glass, strontium-containing glass, zirconium-containing glass, glass ceramic, or fluoroaluminosilicate glass.
[0032] Preferably, the refractive index of the inorganic filler is 1.52 to 1.58, preferably 1.525, 1.53, 1.535, 1.54, 1.545, 1.55, 1.555, 1.56, 1.565, 1.57 or 1.575. The refractive index of the inorganic filler is preferably all other specific point values between the above point values. Due to space limitations and for the sake of brevity, the present invention does not exhaustively recite the specific point values included in the above ranges.
[0033] Preferably, the inorganic filler is a coupling agent modified inorganic filler.
[0034] As a preferred technical solution of the present invention, the inorganic filler provided by the present invention is a coupling agent-modified inorganic filler, which has excellent affinity between the coupling agent-modified inorganic filler and the polymerizable monomer composition, and can further improve the mechanical strength of the cured resin ceramic repair material.
[0035] Preferably, the coupling agent comprises any one or a combination of at least two of γ-methacryloyloxypropyltrimethoxysilane, γ-methacryloyloxypropyltriethoxysilane, or γ-aminopropyltrimethoxysilane, more preferably γ-methacryloyloxypropyltrimethoxysilane.
[0036] Preferably, the resinous ceramic restorative material also includes an additive.
[0037] Preferably, the content of additive in the resin ceramic repair material is 0-5 parts by weight, not 0, preferably 0.1 parts by weight, 0.5 parts by weight, 1 parts by weight, 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight, 3 parts by weight, 3.5 parts by weight, 4 parts by weight, or 4.5 parts by weight. The mass fraction of additive in the resin ceramic repair material is preferably all other specific point values between the above point values. Due to space limitations and for the sake of brevity, the present invention does not exhaustively recite the specific point values included in the above ranges.
[0038] Preferably, the additive comprises any one or a combination of at least two of the following: a colorant, a fluorescent agent, an indicator, a viscosity modifier, a wetting agent, an antioxidant, a stabilizer, or a diluent.
[0039] In a fourth aspect, the present invention provides a method for producing a resin ceramic repair material according to the third aspect, said method comprising reacting a polymerizable monomer composition, an inorganic filler and optional additives to obtain said resin ceramic repair material.
[0040] Preferably, the reaction time is 1 hour or more, preferably 1.1 hours, 1.2 hours, 1.3 hours, 1.4 hours, 1.5 hours, 1.6 hours, 1.7 hours, 1.8 hours, 1.9 hours, or 2 hours. The reaction time is preferably any other specific point value between the above point values. Due to space limitations and for the sake of brevity, the present invention does not exhaustively recite the specific point values included in the range.
[0041] Preferably, the reaction pressure is 1 Mpa or more, preferably 2 Mpa, 3 Mpa, 4 Mpa, 5 Mpa, 6 Mpa, 7 Mpa, 8 Mpa or 9 Mpa. The reaction pressure is preferably all other specific point values between the above point values. Due to space limitations and for the sake of brevity, the present invention does not exhaustively recite the specific point values included in the ranges.
[0042] Preferably, the reaction temperature is 80° C. or higher, preferably 85° C., 90° C., 95° C., 100° C., 105° C., 110° C., 115° C. or 120° C. The reaction temperature is preferably any other specific point value between the above point values. Due to space limitations and for the sake of brevity, the present invention does not exhaustively recite the specific point values included in the ranges.
[0043] The resin ceramic restorative material provided by the present invention can be formed by filling a mold and polymerizing and curing under conditions of heat and pressure.
[0044] A fifth aspect of the present invention is the use of a resin-ceramic restorative material according to the third aspect in a dental restorative material. Effect of the Invention
[0045] Compared with the prior art, the present invention has the following beneficial effects: (1) The polymerizable monomer composition for dental restoration provided by the present invention improves the double bond conversion rate of the polymerizable monomer by adding a crosslinking agent, and reduces the residual polymerizable monomer, thereby increasing the crosslink density of the polymerization system, thereby improving the bending strength and hardness of the polymer, and reducing its water absorption value and solubility value. (2) In the resin ceramic restorative material provided by the present invention, by adding a polymerizable monomer composition containing a crosslinking agent, the obtained resin ceramic restorative material not only maintains its aesthetic appearance, but also improves its properties such as bending strength, water absorption value, and dissolution value. (3) Specifically, the resin ceramic restorative material provided by the present invention has a bending strength of 225 to 274 MPA, an elastic modulus of 10.3 to 11.5 GPa, a Vickers hardness of 102 to 131 HV2.0, and an abrasion resistance of 12.1 to 16.6 mm. 3 The water absorption value is 11-15μg / mm 3 , dissolution value is 0.8-1.2μg / mm 3 The resin ceramic restorative material provided by the present invention has high strength and toughness, so when the material is applied to dental restoration, it can maintain a good shape without collapse, cracking, etc., regardless of the processing process or the patient's wearing and using process. In addition, due to the reduced water absorption value and dissolution value and the improved mechanical strength, its service life is extended and it can be used for permanent restoration, so that the material can be more widely used in dental restoration and meet the needs of the market. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0046] The technical solutions of the present invention are further described below through the detailed description of the embodiments. Those skilled in the art should understand that the above examples are only for helping to understand the present invention, and should not be considered as specific limitations of the present invention. EXAMPLES
[0047] Example 1 1. A polymerizable monomer composition for dental restorations comprising the following components by parts by weight: 70 parts by weight of urethane dimethacrylate, 30 parts by weight of triethylene glycol dimethacrylate, 1 part by weight of benzoyl peroxide, Trimethylolpropane Trimethacrylate 2 parts by weight.
[0048] The manufacturing method thereof is to use urethane dimethacrylate, triethylene glycol dimethacrylate, Trimethylolpropane TrimethacrylateThe above ingredients were uniformly mixed under stirring conditions of 40° C. and a rotation speed of 300 r / min, and then benzoyl peroxide was added and continuously mixed under stirring conditions for 2 hours to obtain the polymerizable monomer composition.
[0049] Example 2 A polymerizable monomer composition for dental restorations comprising, in parts by weight: 60 parts by weight of 2,2-bis(4-(3-(meth)acryloyloxy-2-hydroxypropoxy)phenyl)propane, 40 parts by weight of triethylene glycol dimethacrylate, 1 part by weight of benzoyl peroxide, Trimethylolpropane Trimethacrylate Contains 1 part by weight of the ingredient, The manufacturing method is a process in which 2,2-bis(4-(3-(meth)acryloyloxy-2-hydroxypropoxy)phenyl)propane, triethylene glycol dimethacrylate, and Trimethylolpropane Trimethacrylate and then adding benzoyl peroxide and mixing under stirring for 1 hour to obtain the polymerizable monomer composition.
[0050] Example 3 A polymerizable monomer composition for dental restorations comprising, in parts by weight: 60 parts by weight of 2,2-bis(4-(3-(meth)acryloyloxy-2-hydroxypropoxy)phenyl)propane, 40 parts by weight of triethylene glycol dimethacrylate, 1.2 parts by weight of benzoyl peroxide, 1.5 parts by weight of ethylene glycol dimethacrylate, The preparation method includes uniformly mixing 2,2-bis(4-(3-(meth)acryloyloxy-2-hydroxypropoxy)phenyl)propane, triethylene glycol dimethacrylate and ethylene glycol dimethacrylate under stirring conditions of 50°C and a rotation speed of 300 r / min, and then adding benzoyl peroxide and continuously mixing under stirring conditions for 1.5 hours to obtain the polymerizable monomer composition.
[0051] Example 4 A polymerizable monomer composition for dental restorations comprising, in parts by weight: 60 parts by weight of 2,2-bis(4-(3-(meth)acryloyloxy-2-hydroxypropoxy)phenyl)propane, 40 parts by weight of triethylene glycol dimethacrylate, 1.2 parts by weight of benzoyl peroxide, Contains 5 parts by weight of ethylene glycol dimethacrylate, The manufacturing method is the same as in the first embodiment.
[0052] Example 5 A polymerizable monomer composition for dental restorations comprising, in parts by weight: 70 parts by weight of urethane dimethacrylate, 30 parts by weight of triethylene glycol dimethacrylate, 1 part by weight of benzoyl peroxide, Trimethylolpropane Trimethacrylate Contains 4 parts by weight The manufacturing method is the same as in the first embodiment.
[0053] Example 6 A polymerizable monomer composition for dental restorations comprising, in parts by weight: 65 parts by weight of bisphenol A ethyl methacrylate, 35 parts by weight of triethylene glycol dimethacrylate, 1.5 parts by weight of benzoyl peroxide, Trimethylolpropane Trimethacrylate Contains 3 parts by weight The manufacturing method is the same as in the first embodiment.
[0054] Comparative Example 1 A polymerizable monomer composition for dental restoration, the only difference from Example 1 being: Trimethylolpropane Trimethacrylate The other components, amounts used and production method are all the same as in Example 1.
[0055] Comparative Example 2 A polymerizable monomer composition for dental restoration, the only difference from Example 2 is that Trimethylolpropane Trimethacrylate The other components, amounts used and production method are all the same as in Example 1.
[0056] Comparative Example 3 A polymerizable monomer composition for dental restoration, the only difference from Example 6 is that Trimethylolpropane Trimethacrylate The other ingredients, amounts used and production method are all the same as in Example 6.
[0057] Usage example 1 A resin ceramic restorative material comprising, in parts by weight: 25 parts by weight of a polymerizable monomer composition, Inorganic filler 1 20 parts by weight, Inorganic filler 2 45 parts by weight, Inorganic filler 3: 10 parts by weight
[0058] Here, the polymerizable monomer composition is the polymerizable monomer composition obtained in Example 1, and the inorganic filler 1 is an amorphous barium boroaluminosilicate glass powder (GM27884) modified with γ-methacryloyloxypropyltrimethoxysilane, having a particle diameter D 50 is 1.5 μm, and inorganic filler 2 is an amorphous barium boroaluminosilicate glass powder (GM27884) modified with γ-methacryloyloxypropyltrimethoxysilane, with a particle diameter D 50 is 0.7 μm, inorganic filler 3 is fumed silica (OX-50) modified with γ-methacryloyloxypropyltrimethoxysilane, and the particle diameter D 50 is 40 nm.
[0059] The manufacturing method of the resin ceramic repair material provided in this use example includes reacting a polymerizable monomer composition, an inorganic filler 1, an inorganic filler 2 and an inorganic filler 3 at 15 MPa and 120°C for 2 hours to obtain the resin ceramic repair material.
[0060] Usage example 2 A resin ceramic restorative material comprising, in parts by weight: 20 parts by weight of a polymerizable monomer composition, Inorganic filler 2: 80 parts by weight Here, the polymerizable monomer composition is the polymerizable monomer composition obtained in Example 1, and the inorganic filler 2 is an amorphous barium boroaluminosilicate glass powder (GM27884) modified with γ-methacryloyloxypropyltrimethoxysilane, having a particle diameter D 50 is 0.7 μm, The manufacturing method of the resin ceramic repair material provided in this use example includes reacting the polymerizable monomer composition and the inorganic filler 2 at 15 MPa and 120° C. for 2 hours to obtain the resin ceramic repair material.
[0061] Usage example 3 A resin ceramic restorative material comprising, in parts by weight: 25 parts by weight of a polymerizable monomer composition, Inorganic filler 4 75 parts by weight Here, the polymerizable monomer composition is the polymerizable monomer composition obtained in Example 1, and the inorganic filler 4 is an amorphous barium boroaluminosilicate glass powder (GM27884) modified with γ-methacryloyloxypropyltrimethoxysilane, having a particle diameter D 50 is 0.18 μm, The manufacturing method of the resin ceramic repair material provided in this use example includes reacting the polymerizable monomer composition and the inorganic filler 4 at 15 MPa and 120° C. for 2 hours to obtain the resin ceramic repair material.
[0062] Usage example 4 A resin ceramic restorative material comprising, in parts by weight: 30 parts by weight of a polymerizable monomer composition, Inorganic filler 1 30 parts by weight, Inorganic filler 2 30 parts by weight, Inorganic filler 4: 10 parts by weight Here, the polymerizable monomer composition is the polymerizable monomer composition obtained in Example 2, and the inorganic filler 1 is an amorphous barium boroaluminosilicate glass powder (GM27884) modified with γ-methacryloyloxypropyltrimethoxysilane, having a particle diameter D 50 is 1.5 μm, and inorganic filler 2 is an amorphous barium boroaluminosilicate glass powder (GM27884) modified with γ-methacryloyloxypropyltrimethoxysilane, with a particle diameter D 50 is 0.7 μm, and inorganic filler 4 is an amorphous barium boroaluminosilicate glass powder (GM27884) modified with γ-methacryloyloxypropyltrimethoxysilane, with a particle diameter D 50 is 0.18 μm, The manufacturing method of the resin ceramic repair material provided in this use example includes reacting a polymerizable monomer composition, an inorganic filler 1, an inorganic filler 2 and an inorganic filler 4 at 15 MPa and 120°C for 2 hours to obtain the resin ceramic repair material.
[0063] Usage example 5 A resin ceramic restorative material comprising, in parts by weight: 22 parts by weight of a polymerizable monomer composition, Inorganic filler 4 78 parts by weight Here, the polymerizable monomer composition is the polymerizable monomer composition obtained in Example 2, and the inorganic filler 4 is an amorphous barium boroaluminosilicate glass powder (GM27884) modified with γ-methacryloyloxypropyltrimethoxysilane, having a particle diameter D 50 is 0.18 μm, The manufacturing method of the resin ceramic repair material provided in this use example includes reacting the polymerizable monomer composition and the inorganic filler 4 at 15 MPa and 120° C. for 2 hours to obtain the resin ceramic repair material.
[0064] Usage example 6 A resin ceramic restorative material comprising, in parts by weight: 18 parts by weight of a polymerizable monomer composition, Inorganic filler 2 50 parts by weight, Inorganic filler 3 25 parts by weight, Contains 47 parts by weight of inorganic filler, Here, the polymerizable monomer composition is the polymerizable monomer composition obtained in Example 3, and the inorganic filler 2 is an amorphous barium boroaluminosilicate glass powder (GM27884) modified with γ-methacryloyloxypropyltrimethoxysilane, having a particle diameter D 50 The particle size D50 is 0.7 μm, inorganic filler 3 is fumed silica (OX-50) modified with γ-methacryloyloxypropyltrimethoxysilane, and the particle size D50 is 40 nm, and inorganic filler 4 is amorphous barium boroaluminosilicate glass powder (GM27884) modified with γ-methacryloyloxypropyltrimethoxysilane, and the particle size D50 is 40 nm. 50 is 0.18 μm, The manufacturing method of the resin ceramic repair material provided in this use example includes reacting a polymerizable monomer composition, an inorganic filler 2, an inorganic filler 3 and an inorganic filler 4 at 15 MPa and 120°C for 2 hours to obtain the resin ceramic repair material.
[0065] Usage example 7 A resin ceramic restorative material comprising, in parts by weight: 35 parts by weight of a polymerizable monomer composition, Inorganic filler 3 5 parts by weight, Inorganic filler 4: 60 parts by weight Here, the polymerizable monomer composition is the polymerizable monomer composition obtained in Example 4, the inorganic filler 3 is fumed silica (OX-50) modified with γ-methacryloyloxypropyltrimethoxysilane, and the particle diameter D 50is 40 nm, and inorganic filler 4 is an amorphous barium boroaluminosilicate glass powder (GM27884) modified with γ-methacryloyloxypropyltrimethoxysilane, with a particle diameter D 50 is 0.18 μm, The manufacturing method of the resin ceramic repair material provided in this use example includes reacting the polymerizable monomer composition, the inorganic filler 3 and the inorganic filler 4 at 15 MPa and 120° C. for 2 hours to obtain the resin ceramic repair material.
[0066] Usage example 8 A resin ceramic restorative material comprising, in parts by weight: 20 parts by weight of a polymerizable monomer composition, Inorganic filler 2 50 parts by weight, Inorganic filler 3 5 parts by weight, Inorganic filler 4 25 parts by weight Here, the polymerizable monomer composition is the polymerizable monomer composition obtained in Example 4, and the inorganic filler 2 is an amorphous barium boroaluminosilicate glass powder (GM27884) modified with γ-methacryloyloxypropyltrimethoxysilane, having a particle diameter D 50 is 0.7 μm, inorganic filler 3 is fumed silica (OX-50) modified with γ-methacryloyloxypropyltrimethoxysilane, and the particle diameter D 50 is 40 nm, and inorganic filler 4 is an amorphous barium boroaluminosilicate glass powder (GM27884) modified with γ-methacryloyloxypropyltrimethoxysilane, with a particle diameter D 50 is 0.18 μm, The manufacturing method of the resin ceramic repair material provided in this use example includes reacting a polymerizable monomer composition, an inorganic filler 2, an inorganic filler 3 and an inorganic filler 4 at 15 MPa and 120°C for 2 hours to obtain the resin ceramic repair material.
[0067] Usage example 9 A resin ceramic restorative material comprising, in parts by weight: 25 parts by weight of a polymerizable monomer composition, Inorganic filler 1 20 parts by weight, Inorganic filler 2 45 parts by weight, Inorganic filler 3: 10 parts by weight Here, the polymerizable monomer composition is the polymerizable monomer composition obtained in Example 5, and the inorganic filler 1 is an amorphous barium boroaluminosilicate glass powder (GM27884) modified with γ-methacryloyloxypropyltrimethoxysilane, having a particle diameter D 50 is 1.5 μm, and inorganic filler 2 is an amorphous barium boroaluminosilicate glass powder (GM27884) modified with γ-methacryloyloxypropyltrimethoxysilane, with a particle diameter D 50 is 0.7 μm, inorganic filler 3 is fumed silica (OX-50) modified with γ-methacryloyloxypropyltrimethoxysilane, and the particle diameter D 50 is 40 nm.
[0068] The manufacturing method of the resin ceramic repair material provided in this use example includes reacting a polymerizable monomer composition, an inorganic filler 1, an inorganic filler 2 and an inorganic filler 3 at 15 MPa and 120°C for 2 hours to obtain the resin ceramic repair material.
[0069] Usage example 10 A resin ceramic restorative material comprising, in parts by weight: 25 parts by weight of a polymerizable monomer composition, Inorganic filler 1 70 parts by weight, Contains 2.5 parts by weight of inorganic filler, Here, the polymerizable monomer composition is the polymerizable monomer composition obtained in Example 6, and the inorganic filler 1 is an amorphous barium boroaluminosilicate glass powder (GM27884) modified with γ-methacryloyloxypropyltrimethoxysilane, having a particle diameter D 50 is 0.7 μm, inorganic filler 2 is fumed silica (OX-50) modified with γ-methacryloyloxypropyltrimethoxysilane, and the particle diameter D 50 is 40 nm.
[0070] The manufacturing method of the resin ceramic repair material provided in this use example includes reacting a polymerizable monomer composition, an inorganic filler 1 and an inorganic filler 2 at 15 MPa and 120°C for 2 hours to obtain the resin ceramic repair material.
[0071] Usage example 11 A resin ceramic restorative material comprising, in parts by weight: 25 parts by weight of a polymerizable monomer composition, Inorganic filler 5 20 parts by weight, Inorganic filler 6 45 parts by weight, Inorganic filler 7 10 parts by weight, Here, the polymerizable monomer composition is the polymerizable monomer composition obtained in Example 1, and the inorganic filler 5 is an amorphous barium boroaluminosilicate glass powder (GM27884) having a particle diameter of D 50 is 1.5 μm, and inorganic filler 6 is amorphous barium boroaluminosilicate glass powder (GM27884) with a particle size of D 50 is 0.7 μm, inorganic filler 7 is fumed silica (OX-50), and the particle size is D 50 is 40 nm, and the manufacturing method of the resin ceramic repair material provided in this use example includes reacting a polymerizable monomer composition, an inorganic filler 1, an inorganic filler 2 and an inorganic filler 3 at 15 MPa and 120°C for 2 hours to obtain the resin ceramic repair material.
[0072] Comparative use case 1 This is a resin ceramic restorative material, and the only difference from Use Example 1 is that the polymerizable monomer composition obtained in Comparative Example 1 is used instead of the polymerizable monomer composition obtained in Example 1. All other components, amounts used and manufacturing methods are the same as those in Use Example 1.
[0073] Comparative use case 2 The resin ceramic restorative material is different from Use Example 4 only in that the polymerizable monomer composition obtained in Comparative Example 2 is used instead of the polymerizable monomer composition obtained in Example 2. All other components, amounts used and manufacturing methods are the same as those in Use Example 4. 4 is the same as:
[0074] Comparative use case 3 This is a resin ceramic restorative material, and the only difference from Use Example 10 is that the polymerizable monomer composition obtained in Comparative Example 3 is used instead of the polymerizable monomer composition obtained in Example 6. The other components, amounts used and manufacturing methods are all the same as those of Use Example 10.
[0075] Performance test: (1) Bending strength and elastic modulus: After hardening, the resin ceramic restorative material was cut into test pieces of 1.2 mm × 4.0 mm × 18 mm, and the surfaces of the test pieces were polished by wet grinding with 2000-grit sandpaper. Using a tensile testing machine, a three-point bending test was performed under the conditions of a support interval of 12 mm and a crosshead speed of 1.0 mm / min, and the average values of 10 samples were used for evaluation. (2) Vickers hardness: Using 2000 grit sandpaper, the test surface of the resin ceramic restorative material after curing was polished with water polishing to ensure that the surface of the sample was smooth, and then tested using a Vickers hardness tester: the test force value of "2" was selected, and three different positions of the resin ceramic restorative material were measured, and the average value was obtained. (3) Wear resistance: Using the machining equipment, the resin ceramic restorative material after curing was processed to produce a sample with a diameter of (10±0.1)×(6±0.5)mm. Three samples of various materials were produced, pre-polished with 400-grit sandpaper, the wear load was 22N, and the number of friction times was 75 times. The sandpaper was removed, the tray, the kinetic friction member, the sample, and the fixture were rinsed and wiped dry. Abrasives were used for pre-polishing, and the wear load was 172N, and the sample was rubbed 150 times. After cleaning, it was weighed and recorded as the mass of the sample before polishing m1. A cow's tooth was used to rub the sample 1500 times with a wear load of 172N, and after cleaning, it was weighed and recorded as the mass of the sample after polishing m2. A total of three samples were worn, and the kinetic friction member and the abrasive were replaced before each wear, and the sample density ρ was measured before the measurement, and the volume loss of the sample was ΔV=(m1-m2) / ρ. (4) Water absorption and dissolution values: The hardened resin ceramic restorative material was processed into samples with a size of φ(15±1)×(1.0±0.2) mm, and the surface of the sample was polished by wet grinding with 2000-grit sandpaper. The diameter and thickness of the sample were measured, and the volume V of the sample was calculated. The sample was then placed in a desiccator and dried in an oven at 37°C. After 24 hours, the samples were taken out and weighed one by one on a 1 / 10,000 balance with an accuracy of 0.1 mg. The above steps were repeated until a constant weight was reached, and recorded as m1. The constant weight sample was placed in a zippered storage bag containing about 30 mL of pure water, and immersed in a thermostatic water bath at 37±1°C. After immersion for 7 days, it was taken out, rinsed with clean water, and then the surface was dried before testing, weighed on a 1 / 10,000 balance, and recorded as m2. Finally, it was placed in a 37°C oven to dry for 14-21 days until a constant weight was reached, and weighed on a 1 / 10,000 balance, and recorded as m3. Water absorption value ρ ws =(m2-m3) / V, solubility value ρ sl =(m1-m3) / V.
[0076] The resin ceramic restorative materials corresponding to the resin ceramic restorative materials obtained in Use Examples 1 to 11 and Comparative Use Examples 1 to 3 were tested according to the above test method, and the test results are shown in Table 1. [Table 1] Performance parameters of the resin ceramic restorative materials obtained in Use Examples 1 to 11 and Comparative Use Examples 1 to 3
[0077] [Table 1]
[0078] According to the data in Table 1, the resin ceramic restorative materials obtained by adding the crosslinking agent in Examples 1 to 10 have a bending strength of 225 to 274 MPa, an elastic modulus of 10.3 to 11.5 GPa, a Vickers hardness of 102 to 131 HV2.0, and abrasion resistance of 12.1 to 16.6 mm. 3 The resin ceramic restorative materials obtained in Comparative Examples 1 to 3 had a bending strength of only 190 to 212 MPa, an elastic modulus of 7.5 to 8.2 GPa, a Vickers hardness of 75 to 87 HV2.0, and abrasion resistance of 19.6 to 22.7 mm. 3 This demonstrates the superior mechanical properties of the resin-ceramic restorative material provided by the present invention.
[0079] In addition, the water absorption values of the resin ceramic restorative materials obtained in Examples 1 to 10 were 11 to 15 μg / mm 3 , the dissolution value is 0.8-1.2μg / mm 3 These values are obviously lower than the water absorption and dissolution values of the resin ceramic restorative materials obtained in Comparative Examples 1 and 2, which demonstrates that the resin monomer residue in the resin ceramic restorative material obtained by the present invention is low.
[0080] In addition, when comparing Use Example 1 and Use Example 11, it was found that the resin ceramic restorative material obtained by adding a filler that was not modified with a coupling agent had poor mechanical properties, water absorption, and solvent resistance.
[0081] In summary, it can be seen that the resin-ceramic restorative material provided by the present invention has excellent mechanical properties, biocompatibility, safety, and long service life.
[0082] The applicant declares that the present invention describes the polymerizable monomer composition for dental restoration and its preparation method and use through the above examples, but the present invention is not limited to the above examples, that is, it does not mean that the present invention must be implemented based on the above examples. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of each raw material of the product of the present invention, addition of auxiliary components, selection of specific methods, etc. are all within the protection scope and disclosure scope of the present invention.
Claims
1. A resin ceramic repair material, the resin ceramic repair material comprising a combination of a polymerizable monomer composition and an inorganic filler; The polymerizable monomer composition includes, in parts by weight, 20 to 100 parts by weight of a polymerizable monomer, 0.01 to 10 parts by weight of an initiator, and 0.01 to 10 parts by weight of a crosslinking agent; The initiator includes any one or a combination of at least two of dicumyl peroxide, tert-butyl peroxide, benzoyl peroxide, lauroyl peroxide, tert-butyl peracetate, butyl tert-peroxybenzoate, pivaloyl tert-butyl peroxide, potassium persulfate, sodium persulfate, ammonium persulfate, azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile) or 2,2'-azobis(2-methylpropionate)dimethyl; The crosslinking agent includes any one or a combination of at least two of trimethylolpropane trimethacrylate or ethylene glycol dimethacrylate; The inorganic filler is a coupling agent-modified inorganic filler, The polymerizable monomers include methyl methacrylate, ethyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, isoamyl methacrylate, benzyl methacrylate, glycidyl methacrylate, dodecyl methacrylate, tetrahydrofurfuryl methacrylate, 2-(dimethylamino)ethyl methacrylate, 2,3-dibromopropyl 2-methylpropenoate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 6-hydroxyhexyl methacrylate, and 10-hydroxydecyl methacrylate. , triethylene glycol monomethacrylate, triethyl glycol dimethacrylate, propylene glycol monomethacrylate, ethylene glycol methacrylate, diethylene glycol methacrylate, methoxydiethylene glycol methacrylate, polyethylene glycol methacrylate, N-methylol (meth)acrylamide, N-succinyl (meth)acrylamide, 10-(meth)acryloyloxydecyl dihydrogen phosphate, propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylamide acrylate, butanediol di(meth)acrylate, hexanediol di(meth)acrylate, polyethylene glycol di(meth)acrylate, urethane dimethacrylate, bisphenol A ethyl methacrylate, bisphenol A glycidyl (meth)acrylate (2,2-bis[4-[3-(meth)acryloyloxy-2-hydroxypropoxy]phenyl]propane), 2,2-bis[4-(meth)acryloyloxyethoxyphenyl]propane, 2,2-bis(4-(meth)acryloyloxydiethoxyphenyl)propane the compound includes any one or a combination of at least two of N,N'-(2,2,4-trimethylhexamethylene)bis[2-(aminocarboxy)propane-1,3-diol]tetramethacrylate, trimethylolethane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and N,N'-(2,2,4-trimethylhexamethylene)bis[2-(aminocarboxy)propane-1,3-diol]tetramethacrylate, The resin ceramic restorative material has a density of 11 to 15 μg / mm 3 and a water absorption value of 0.8 to 1.2 μg / mm 3 4. A resin ceramic restorative material having a dissolution value of
2. 2. The resin ceramic restorative material according to claim 1, wherein the refractive index of the polymerizable monomer after polymerization is 1.52 to 1.
58.
3. The resinous ceramic restorative material comprises, in parts by weight, 10-90 parts by weight of a polymerizable monomer composition and 10-90 parts by weight of an inorganic filler, or the inorganic filler comprises any one or a combination of at least two of silica, aluminum silicate, alumina, calcium fluoride, strontium fluoride, calcium carbonate, kaolin, clay, mica, aluminum sulfate, calcium sulfate, barium sulfate, titanium oxide, calcium phosphate, hydroxyapatite, calcium hydroxide, strontium hydroxide, zeolite, titanium dioxide, or zirconia; or the resin ceramic restorative material comprises, by weight, 10-90 parts by weight of a polymerizable monomer composition and 10-90 parts by weight of an inorganic filler, the inorganic filler comprising any one or a combination of at least two of silica, aluminum silicate, alumina, calcium fluoride, strontium fluoride, calcium carbonate, kaolin, clay, mica, aluminum sulfate, calcium sulfate, barium sulfate, titanium oxide, calcium phosphate, hydroxyapatite, calcium hydroxide, strontium hydroxide, zeolite, titanium dioxide, or zirconia; or The inorganic filler may include any one or a combination of at least two of silica, aluminum silicate, alumina, calcium fluoride, strontium fluoride, calcium carbonate, kaolin, clay, mica, aluminum sulfate, calcium sulfate, barium sulfate, titanium oxide, calcium phosphate, hydroxyapatite, calcium hydroxide, strontium hydroxide, zeolite, titanium dioxide, or zirconia, and the inorganic filler may also include a glass inorganic filler, or the resin ceramic restorative material may include 10 to 90 parts by weight of a polymerizable monomer composition. and 10 to 90 parts by weight of an inorganic filler, the inorganic filler including any one or a combination of at least two of silica, aluminum silicate, alumina, calcium fluoride, strontium fluoride, calcium carbonate, kaolin, clay, mica, aluminum sulfate, calcium sulfate, barium sulfate, titanium oxide, calcium phosphate, hydroxyapatite, calcium hydroxide, strontium hydroxide, zeolite, titanium dioxide, or zirconia, the inorganic filler also including a glass inorganic filler, or the inorganic filler including silica,The inorganic filler may include any one or a combination of at least two of aluminum silicate, alumina, calcium fluoride, strontium fluoride, calcium carbonate, kaolin, clay, mica, aluminum sulfate, calcium sulfate, barium sulfate, titanium oxide, calcium phosphate, hydroxyapatite, calcium hydroxide, strontium hydroxide, zeolite, titanium dioxide, and zirconia, and the inorganic filler may also include a glass inorganic filler, and the glass inorganic filler may be fluorine glass, borosilicate glass, soda glass, barium glass, barium aluminate, or the like. or a combination of at least two of silicate glass, strontium-containing glass, zirconium-containing glass, glass ceramic, or fluoroaluminosilicate glass; or the resin ceramic restorative material comprises, by weight, 10-90 parts by weight of a polymerizable monomer composition and 10-90 parts by weight of an inorganic filler, the inorganic filler being selected from the group consisting of silica, aluminum silicate, alumina, calcium fluoride, strontium fluoride, calcium carbonate, kaolin, clay, mica, aluminum sulfate, calcium sulfate, barium sulfate, titanium dioxide, lithium. The inorganic filler may include any one or a combination of at least two of calcium phosphate, hydroxyapatite, calcium hydroxide, strontium hydroxide, zeolite, titanium dioxide, or zirconia, and the inorganic filler may also include a glass inorganic filler, and the glass inorganic filler may include any one or a combination of at least two of fluorine glass, borosilicate glass, soda glass, barium glass, barium aluminosilicate glass, strontium-containing glass, zirconium-containing glass, glass ceramic, or fluoroaluminosilicate glass. or the refractive index of said inorganic filler is 1.52-1.58; or said resin ceramic restorative material comprises, in parts by weight, 10-90 parts by weight of a polymerizable monomer composition and 10-90 parts by weight of an inorganic filler, and the refractive index of said inorganic filler is 1.52-1.58; or said inorganic filler is selected from the group consisting of silica, aluminum silicate, alumina, calcium fluoride, strontium fluoride, calcium carbonate, kaolin, clay, mica, aluminum sulfate, calcium sulfate, barium sulfate, titanium oxide, calcium phosphate, hydroxyapatite, calcium hydroxide,or the resin ceramic restorative material comprises, in parts by weight, 10-90 parts by weight of a polymerizable monomer composition and 10-90 parts by weight of an inorganic filler, the inorganic filler being selected from the group consisting of silica, aluminum silicate, alumina, calcium fluoride, strontium fluoride, calcium carbonate, kaolin, clay, mica, aluminum sulfate, sulfur, and the like. The inorganic filler may include any one or a combination of at least two of the following: calcium hydroxide, barium sulfate, titanium oxide, calcium phosphate, hydroxyapatite, calcium hydroxide, strontium hydroxide, zeolite, titanium dioxide, or zirconia; the inorganic filler may also include a glass inorganic filler; the refractive index of the inorganic filler may be 1.52 to 1.58; or the inorganic filler may include silica, aluminum silicate, alumina, calcium fluoride, strontium fluoride, calcium carbonate, kaolin, clay, mica, aluminum sulfate, calcium sulfate, barium sulfate, titanium dioxide, or zirconia. The inorganic filler may include any one or a combination of at least two of the following: calcium, titanium oxide, calcium phosphate, hydroxyapatite, calcium hydroxide, strontium hydroxide, zeolite, titanium dioxide, or zirconia; the inorganic filler may also include a glass inorganic filler; the glass inorganic filler may include any one or a combination of at least two of the following: fluorine glass, borosilicate glass, soda glass, barium glass, barium aluminosilicate glass, strontium-containing glass, zirconium-containing glass, glass ceramic, or fluoroaluminosilicate glass; or the resin ceramic restorative material comprises, in parts by weight, 10-90 parts by weight of a polymerizable monomer composition and 10-90 parts by weight of an inorganic filler, the inorganic filler being selected from the group consisting of silica, aluminum silicate, alumina, calcium fluoride, strontium fluoride, calcium carbonate, kaolin, clay, mica, aluminum sulfate, calcium sulfate, barium sulfate, titanium oxide, calcium phosphate, hydroxyapatite, calcium hydroxide, strontium hydroxide, zeolite,or a combination of at least two of titanium dioxide or zirconia; the inorganic filler also includes a glass inorganic filler, the glass inorganic filler including any one or a combination of at least two of fluorine glass, borosilicate glass, soda glass, barium glass, barium aluminosilicate glass, strontium-containing glass, zirconium-containing glass, glass ceramic, or fluoroaluminosilicate glass; the refractive index of the inorganic filler is 1.52 to 1.58; or the coupling agent includes any one or a combination of at least two of gamma-methacryloyloxypropyltrimethoxysilane, gamma-methacryloyloxypropyltriethoxysilane, or gamma-aminopropyltrimethoxysilane; or the resin ceramic repair material includes 10 to 90 parts by weight of a polymerizable monomer composition and 10 to 90 parts by weight of an inorganic filler; the coupling agent includes gamma-methacryloyloxypropyltrimethoxysilane, gamma-methacryloyloxypropyltriethoxysilane, or gamma-aminopropyltrimethoxysilane; The resin ceramic repair material according to claim 1 or 2, characterized in that the resin ceramic repair material also includes an additive, or the resin ceramic repair material also includes an additive, and the content of the additive in the resin ceramic repair material is 0 to 5 parts by weight and is not 0, or the resin ceramic repair material also includes an additive, and the additive includes any one or at least two combinations of a colorant, a fluorescent agent, an indicator, a viscosity modifier, a wetting agent, an antioxidant, a stabilizer, or a diluent, or the resin ceramic repair material also includes an additive, and the content of the additive in the resin ceramic repair material is 0 to 5 parts by weight and is not 0, and the additive includes any one or at least two combinations of a colorant, a fluorescent agent, an indicator, a viscosity modifier, a wetting agent, an antioxidant, a stabilizer, or a diluent.
4. 2. A method for producing a resin ceramic repair material according to claim 1, comprising reacting a polymerizable monomer composition, an inorganic filler and optional additives to obtain the resin ceramic repair material, The reaction time is 1 hour or more and 2 hours or less, or the reaction pressure is 1 MPa or more and 15 MPa or less, or the reaction time is 1 hour or more and 2 hours or less and the reaction pressure is 1 MPa or more and 15 MPa or less, or the reaction temperature is 80°C or more and 120°C or less, or the reaction time is 1 hour or more and 2 hours or less and the reaction temperature is 80°C or more and 120°C or less.
5. Use of the resin ceramic restorative material according to claim 4 as a dental restorative material.
Citation Information
Patent Citations
Dental compositions, mill blocks, and methods
CN102665605A
Dental curable composition including chain transfer agent
CN105310889A
Polymerizable monomer composition for dental material
CN106132383A
Composite resin material composition for dentistry cutting containing chain transfer agent
JP2016013997A
A balanced denture system containing hard compositions
JP2019505580A